Peran matriks metaloproteinase-8 pada cairan krevikuler gingiva selama pergerakan gigi ortodontik - Susilowati Susilowati (DiscoverSys Inc., 2010)
Orthodontic treatment usually involves tooth movement. The orthodontic force as anextrinsic mechanical stimulus, evokes a biologic cellular response in the periodontalsupporting ligament. At early stage, it causes inflammation of periodontal tissuewhich is followed by the release of cytokines, T cell, B cell, and then MMP enzyme.MMP-8 (collagenase 2) is a member of matrixin subfamily plays an important role inperiodontal ligament remodeling. It has capability to maintain the cellular structure,integrity, activity, and function of extracellular matrix of periodontal tissue. The maincomponent of extracellular matrix is tissue protein, i.e. collagen, fibronectin, andglicosaminoglycan. During orthodontic tooth movement, collagen degradation occursin extracellular matrix of periodontal tissue and alveolar bone. As a result, it enablesthe release of cells from extracellular environment, for example osteoblast moves toapposition and osteoclast to resorption sites that enable the tooth movement. Theexpression and level of MMP-8 can be assessed in the gingival crevicular fluid. Theaim of this review is to describe the role of MMP-8 in orthodontic tooth movement.